Continuous and sustainable cellulose filaments from ionic liquid dissolved paper sludge nanofibres. (20th January 2021) - Adu, Cynthia; Zhu, Chenchen; Jolly, Mark; Richardson, Robert M.; Eichhorn, Stephen J.
Abstract: The textile industry is resource-intensive, which has a significant impact on global emissions and waste pollution. To meet the demand of textiles over a third of fibres used in manufacturing are sourced from fossil fuels. As the global demand for textiles continues to grow, manufacturers are having to seek innovative approaches to providing sustainable and regenerative cellulose fibres. However, the latest climate change pressures on the textile industry have uncovered grave environmental issues associated with traditional regenerative cellulose production, such as the viscose manufacturing process. The viscose process requires intensive use of hazardous chemicals which leads to water pollution and ecotoxicity. In addition, if forestry products are unsustainably sourced for this process, this can lead to resource scarcity and deforestation. To provide a holistic solution for mitigating these challenges this study uses the by-products of paper manufacturing dissolved in an ionic liquid to produce regenerated cellulose filaments. Paper mill sludge (PMS) is a cellulosic by-product typically used on animal bedding and land spreading. The material has been dissolved in an ionic liquid - 1-ethyl-3-methylimidazolium diethyl phosphate - with the aid of a co-solvent dimethyl sulfoxide (DMSO) - and spun into continuous filaments for textile production. The mechanical properties of paper sludge filaments are found to be competitive with commercial viscose, which is promising for their drop-in replacement. It is also demonstrated that by increasing the concentration of the PMS from 9% to 12.4%, an improvement of the filament properties can be achieved; an increase in modulus from ∼19 GPa to ∼26 GPa and strength from ∼223 MPa to ∼282 MPa. These values are shown to be competitive with other commercial, less sustainable, regenerated cellulose fibres. Graphical abstract: Image 1